Antibody response to chlamydiae in children with asthma and respiratory illness - Kazár, J; Kováčová, E; Gašparovič, J; Cervenka, J; Furková, K; Hornová, J; Wimmerová, S (Folia microbiologica, 2011)
No relation between the occurrence of antibodies to chlamydial agents and asthma in children was found. In asthmatic children, the antibodies to Chlamydia trachomatis occurred in 3.1% and to Chlamydophila pneumoniae in 22.7%, whereas in a control group of children without asthma or other allergic disease in 2.3% and 24.0%, respectively. The occurrence of antibodies of IgA and IgG classes to C. pneumoniae was also very similar; its rise was age-dependent. On the other hand, in the group of children in a pre-school age with respiratory tract infection, anti-chlamydial antibodies were demonstrated significantly more often (18.5% of IgG antibodies to C. trachomatis, 20.0% of IgM antibodies to both C. trachomatis and C. pneumoniae) than in those suffering from other, non-respiratory illness (3.9% of the former and 5.9% of the latter antibodies). However, in these children, we did not succeed in detection of C. trachomatis in conjunctival and nasopharyngeal smears by PCR. Nevertheless, chlamydial agents (C. trachomatis in infants, C. pneumoniae in pre-school children) should be taken into consideration in a differential diagnosis of respiratory tract inflammation.
Keywords: Asthma; bronchiální astma; Humans; konjunktiva; Respiratory Tract Infections; imunoglobulin G; dítě; Chlamydophila pneumoniae; Child; chlamydiové infekce; protilátky bakteriální; ELISA; lidé; Immunoglobulin A; Enzyme-Linked Immunosorbent Assay; Antibodies, Bacterial; předškolní dítě; Nasopharynx; Adolescent; infekce dýchací soustavy; nazofarynx; imunoglobulin A; Chlamydia trachomatis; imunoglobulin M; Conjunctiva; Child, Preschool; Immunoglobulin G; Chlamydia Infections; Immunoglobulin M; mladiství